Relative larvicidal potential of Pseudocalymma alliaceum and Allium sativum against malaria vector, Anopheles stephensi (Liston). Issue 30 (2012) - Bhan, Sweta; Sharma, Preeti; Mohan, Lalit; Srivastava, Chand Narayan
No abstract available